A partir de los movimientos de un pájaro... La «danza de la perdiz» en los rituales ganaderos de los Andes peruanos - Rivera Andía, Juan Javier (Revista Española de Antropología Americana, 2012)
This paper presents a brief look at the conception of a bird that the people of the central Andes of Peru have. We explore this perspective through the collective representations found in a ritual and in beliefs and stories about this animal in the mountains of Lima. In this way we hope to contribute to the knowledge about the role played by certain animals in the Andean ways of thinking of Amerindian roots.<br
Keywords: Intangible patrimony; Andes; birds; fauna; ethnozoology; ritual; oral tradition.